Reduções em Família e Multiplicidades Mistas - Sarria, Luis Alberto Alba (2009)
Let (R,m) be a Noetherian local ring. Mixed multiplicities of finitely many m-primary ideals were first defined by J. Risler and B. Teissier in [Teissier] and they proved that these could be described as the usual Hilbert-Samuel multiplicity of the ideal generated by an appropriated superficial sequence. This result was later generalized by D. Rees in [Rees], who first introduced the notion of joint reduction for a family of ideals and proved that the mixed multiplicities of a family of m-primary ideals could be described as the Hilbert-Samuel multiplicity of the ideal generated by a suitable joint reduction. This theorem is known as Rees mixed multiplicity theorem and it is a crucial result in the theory of mixed multiplicities for m-primary ideals. The converse of Rees theorem was given by I. Swanson in her Ph. D. thesis (see [Swanson]). In this work, we give a detailed proof of all of the above mentioned results.